Differences in muscle activity and fatigue of the upper limb between Task-Specific training and robot assisted training among individuals post stroke. (24th May 2019) - Shahar, Neta; Schwartz, Isabella; Portnoy, Sigal
Abstract: Objective: To compare the activity and fatigue of upper extremity muscles, pain levels, subject satisfaction levels, perceived exertion, and number of repetitions in Task-Specific Training (TST) compared with Robot-Assisted Training (RAT) in individuals post-stroke. Methods: Twenty sub-acute post stroke subjects (16 men; median (interquartile range) age 64.0 (71.5–57.0) years) received two 30-min treatment sessions, one TST and one RAT. Before each session, the Visual Analogue Scale (VAS) was administered. Activity levels and fatigue of six muscles were monitored using surface electromyography and the number of repetitions was counted. After each session, the subjective assessment questionnaire of treatment, the Borg scale and VAS were administered. Results: During TST, the Anterior Deltoid, Upper Trapezius and Biceps were more active, while during the RAT, the Triceps was more active. The Triceps activity increased during TST towards the end of the session. The pain levels increased after TST and the number of repetitions was higher compared to RAT. There were no significant differences in muscle fatigue, perceived physical exertion and subject satisfaction levels between both treatment sessions. Conclusion: This is the first study to explore the biomechanics of both treatment methods and might therefore shed light on the mechanisms behind their positive outcomes. Due to the differences in the biomechanics of the treatments, a combination of both treatments may be beneficial to the activation of different muscle groups, thereby contributing to the rehabilitation program post stroke.